2023
DOI: 10.1021/acscatal.2c05363
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Density-Dependent Activity of Cu Single-Atom Catalyst in the Benzene Hydroxylation Reaction

Abstract: Regulating the density of metal single atoms and exploring the interaction among them are showing great potential to further raise the performance of single-atom catalysts (SACs). Herein, we produce a series of Cu SACs with densities ranging from 0.1 to 2.4 atoms/nm 2 and find that the catalytic activity is proportional to Cu single-atom density in the benzene hydroxylation reaction. Mechanistic studies reveal that the interactions among neighboring single-atom moieties in ultra-high-density Cu SAC alter the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 46 publications
0
35
0
Order By: Relevance
“…Figure a demonstrates electron accumulation between central Ir and P atoms, similar to other single-atom materials with P coordination in the literature. , Moreover, when the Ir density increases, more average localized charge gathers around Ir sites, causing the Ir valence shift to metallic state, which is consistent with the XANES and XPS results (Figure a,b). These charge density differences indicated the interaction among these single sites in densely populated SACs through charge redistribution, resulting in different electronic structures, which would affect the reactant/intermediate adsorption/desorption and, consequently, catalytic performance.…”
Section: Resultsmentioning
confidence: 99%
“…Figure a demonstrates electron accumulation between central Ir and P atoms, similar to other single-atom materials with P coordination in the literature. , Moreover, when the Ir density increases, more average localized charge gathers around Ir sites, causing the Ir valence shift to metallic state, which is consistent with the XANES and XPS results (Figure a,b). These charge density differences indicated the interaction among these single sites in densely populated SACs through charge redistribution, resulting in different electronic structures, which would affect the reactant/intermediate adsorption/desorption and, consequently, catalytic performance.…”
Section: Resultsmentioning
confidence: 99%
“…A two-step strategy incorporating polycondensation and subsequent pyrolysis procedures was developed to synthesize the densely populated metal SACs (Supplementary Fig. 1 , details are shown in the Experimental Section) 32 . The key success of this strategy relies on the controllable polycondensation during the first step, whereby the small molecules (melamine, cyanuric acid, l -alanine and phytic acid) are spontaneously polymerized in water to form two-dimensional nanosheets (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These examples indicated that the interactions among single sites in densely populated SACs could indeed synergize to further regulate the electronic structure and reactivity in various reactions 20 , 31 , 32 . However, the underlying mechanisms were distinct, and there was no unified theoretical guidance available at the same time.…”
Section: Introductionmentioning
confidence: 95%
“…In addition to the coordination environment engineering, regulating the density of metal single atoms is also of vital importance for affecting the catalytic performance of Cu SACs. Aiming to better understand the density-dependent activity of Cu SACs in the benzene hydroxylation reactions, Song et al 95 reported the synthesis of a series of Cu SACs with the densities ranging from 0.1 to 2.4 atoms per nm 2 and found that the catalytic activity of Cu SACs was proportional to Cu single-atom density in the benzene hydroxylation reaction (Fig. 9a–d).…”
Section: Single-atom Catalysts For Benzene Oxidation To Phenolmentioning
confidence: 99%